Tanzania Economic Update, October 2012 : Spreading the Wings - World Bank (World Bank, Washington, DC, 2017)
Tanzania continues to stand out as a model of sound economic performance in the African continent, with a growth rate of over six per cent in 2011 and 2012, surpassing other regional economies and demonstrating impressive resilience to the global economic crisis. This is the second issue of the Tanzania economic update series. The series aim to engage a broad audience in a discussion of the state of the economy in general, as well as in specific debates of topical importance in Tanzania. The current issue seeks to get the discussion going on how to achieve the structural transformation of the rural economy so that rural households can also benefit from the country's remarkable growth performance.